Effects of a soft robotic exosuit on the quality and speed of overground walking depends on walking ability after stroke - Sloot, Lizeth H.; Baker, Lauren M.; Bae, Jaehyun; Porciuncula, Franchino; Clément, Blandine F.; Siviy, Christopher; Nuckols, Richard W.; Baker, Teresa; Sloutsky, Regina; Choe, Dabin K.; O’Donnell, Kathleen; Ellis, Terry D.; et al. (Journal of neuroEngineering and rehabilitation, 2023)
Soft robotic exosuits can provide partial dorsiflexor and plantarflexor support in parallel with paretic muscles to improve poststroke walking capacity. Previous results indicate that baseline walking ability may impact a user’s ability to leverage the exosuit assistance, while the effects on continuous walking, walking stability, and muscle slacking have not been evaluated. Here we evaluated the effects of a portable ankle exosuit during continuous comfortable overground walking in 19 individuals with chronic hemiparesis. We also compared two speed-based subgroups (threshold: 0.93 m/s) to address poststroke heterogeneity.
Gesehen am 08.12.2023